The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1096/fj.00-0043com
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of protein (collagen) synthesis in sponge cells by a cardiac myotrophin‐related molecule from Suberites domuncula

Abstract: The body wall of sponges (Porifera), the lowest metazoan phylum, is formed by two epithelial cell layers of exopinacocytes and endopinacocytes, both of which are associated with collagen fibrils. Here we show that a myotrophin-like polypeptide from the sponge Suberites domuncula causes the expression of collagen in cells from the same sponge in vitro. The cDNA of the sponge myotrophin was isolated; the potential open reading frame of 360 nt encodes a 120 aa long protein (Mr of 12,837). The sequence SUBDOMYOL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…The data presented above demonstrate that at suitable concentrations silicate induces the genes encoding collagen, silicatein and myotrophin. However, the gene induction of silicatein appears to be a complex process, since the morphogen myotrophin induces only the collagen, but not the silicatein gene Schröder et al 2000). This finding supports earlier observations indicating that the formation of collagen fibrils can proceed independently of spicule formation as well as closely connected with this process (reviewed in: Simpson 1984).…”
Section: Proposed Pathway For Spicule Formationsupporting
confidence: 88%
“…The data presented above demonstrate that at suitable concentrations silicate induces the genes encoding collagen, silicatein and myotrophin. However, the gene induction of silicatein appears to be a complex process, since the morphogen myotrophin induces only the collagen, but not the silicatein gene Schröder et al 2000). This finding supports earlier observations indicating that the formation of collagen fibrils can proceed independently of spicule formation as well as closely connected with this process (reviewed in: Simpson 1984).…”
Section: Proposed Pathway For Spicule Formationsupporting
confidence: 88%
“…Three segments can be distinguished: (i) the N-terminal non-collagen region (aa 1 to aa 26 ); (ii) the region comprising the characteristic G-X-Y collagen triple helix repeats (in COLL3_SUBDO 37 triples; aa 27-136 ); and finally (iii) the non-collagen C-terminal part (aa ). This arrangement has been described also for the other collagen proteins from S. domuncula (15,37). Data bank searches revealed that COLL3_SUBDO shares highest sequence similarity to the fibrillar collagen from Haliotis discus (BAA75668 (38)) with E ϭ 8e Ϫ39 and from…”
Section: Co-expression Of Silicatein With Galectin and Collagensupporting
confidence: 62%
“…Until now, only genes encoding non-fibrillar collagens had been described in sponges, e.g. as for Ephydatia muelleri (40) or S. domuncula (37). The newly discovered S. domuncula collagen displays the typical structure for fibrillar collagens: the N-peptide, the triple helix segment, and the C-peptide.…”
Section: Discussionmentioning
confidence: 99%
“…This cDNA was used for expression in Escherichia coli as described. 53,69 The cDNA was inserted into the bacterial oligohistidine expression vector pQE-32 (Quiagen). E. coli (XL1-blue) were transformed with this plasmid and expression of fusion protein was induced with isopropyl 1-thio-b-Dgalactopyranoside (IPTG).…”
Section: Northern Blot Analysismentioning
confidence: 99%